2013
DOI: 10.1016/j.jip.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis Cry1Ia10 and Vip3Aa protein interactions and their toxicity in Spodoptera spp. (Lepidoptera)

Abstract: The polyphagous pests belonging to the genus Spodoptera are considered to be among the most important causes of damage and are widely distributed throughout the Americas'. Due to the extensive use of genetically modified plants containing Bacillus thuringiensis genes that code for insecticidal proteins, resistant insects may arise. To prevent the development of resistance, pyramided plants, which express multiple insecticidal proteins that act through distinct mode of actions, can be used. This study analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 51 publications
4
51
1
1
Order By: Relevance
“…Synergism has been observed between the Vip3Aa and Cyt2Aa proteins against Chilo suppressalis (Lepidoptera: Crambidae) and S. exigua after their coexpression in Escherichia coli; contrarily, this protein combination was slightly antagonistic against C. quinquefasciatus (66). Bergamasco et al (74) reported synergism between Vip3A and Cry1Ia in three Spodoptera species (S. frugiperda, S. albula, and S. cosmioides [Lepidoptera: Noctuidae]) but slight antagonism in Spodoptera eridania (Lepidoptera: Noctuidae). Antagonism between the Vip3A and Cry1A or Cry1Ca proteins in H. virescens was described (75): antagonism was found for the combination of Cry1Ca and Vip3Aa, Vip3Ae, or Vip3Af and for the combination of Vip3Af and either Cry1Aa or Cry1Ac.…”
Section: Insecticidal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Synergism has been observed between the Vip3Aa and Cyt2Aa proteins against Chilo suppressalis (Lepidoptera: Crambidae) and S. exigua after their coexpression in Escherichia coli; contrarily, this protein combination was slightly antagonistic against C. quinquefasciatus (66). Bergamasco et al (74) reported synergism between Vip3A and Cry1Ia in three Spodoptera species (S. frugiperda, S. albula, and S. cosmioides [Lepidoptera: Noctuidae]) but slight antagonism in Spodoptera eridania (Lepidoptera: Noctuidae). Antagonism between the Vip3A and Cry1A or Cry1Ca proteins in H. virescens was described (75): antagonism was found for the combination of Cry1Ca and Vip3Aa, Vip3Ae, or Vip3Af and for the combination of Vip3Af and either Cry1Aa or Cry1Ac.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…10). Specific binding to brush border membrane vesicles (BBMVs) prepared from susceptible insects was first shown by using biotin-labeled Vip3Aa and Vip3Af (68,69,74,87,92,93,95). Interestingly, Vip3Aa also binds specifically to BBMVs of the nonsusceptible insect O. nubilalis (87), which indicates that specific binding is not sufficient to produce toxicity.…”
Section: Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a strong synergistic interaction was found between these two factors towards D. pini, indicating that formulations containing both proteins can be effective in combating this dangerous pest of conifers. Several authors have also observed synergisms and high insecticidal activity of Vip and crystal toxin mixtures against different lepidopteran pests: Anticarsia gemmatalis, Chrysodeixis includes (Crialesi- , S. albula, S. cosmoides, S. frugiperda (Bergamasco et al 2013), S. exigua, C. suppressalis (Yu et al 2012) and Diatraea saccharalis . However, the authors have also noticed antagonistic Cry/Vip interactions in other insects.…”
Section: Discussionmentioning
confidence: 98%
“…Metarhizium anisopliae is also known as an entomopathogenic fungus and is applied to control insect pests; Metarhizium anisopliae-extracted toxin, destruxin, is lethal to insects (Sharif, 2010;Smagghe et al, 2013). Bacillus thuringiensis is a widely represented entomopathogenic bacterium that produce crystal (Cry) toxins 1, 2, 4, 10, and 11 and is used as the first choice effective biological control against many kinds of insects from the orders Coleoptera, Lepidoptera, and Diptera (Ben-Dov, 2014;Bergamasco et al, 2013). we assumed that it originated from coconut palm rhinoceros beetle O. rhinoceros (Lee et al, 2015).…”
mentioning
confidence: 99%